A strain softening resistant zinc alloy and its preparation method and application
Patent Information
- Application Number
- CN202410113174.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-01-26
AI Technical Summary
[0006]本发明要解决的问题是:提供一种抗应变软化锌合金及其制备方法和应用,以解决现有的锌基合金应变软化的问题
[0026](1)本发明的抗应变软化锌合金在保证较好的屈服强度及抗拉强度下,还具有较好的断裂延伸率和均匀延伸率,有效克服了锌基合金存在的应变软化缺陷;可应用于心血管支架材料等需具有循环载荷性能的种植材料。
Smart Images

Figure CN117867326B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical biodegradable metal materials technology, specifically relating to a strain-resistant zinc alloy, its preparation method, and its application. Background Technology
[0002] Traditional medical metals (such as titanium, stainless steel, and tantalum) are widely used as implant materials in clinical practice due to their ability to provide sufficient mechanical support. However, the permanent presence of these metals in the body increases the risk of inflammation and infection, often requiring removal after a certain period of use, thus increasing treatment costs and infection risks. Therefore, novel biodegradable metals that can promote tissue healing have attracted much attention. There are three main types of novel biodegradable metals: Mg, Zn, and Fe. Among them, Zn's degradation rate is between that of Mg and Fe, making it a metal with good development prospects. However, pure zinc lacks sufficient mechanical strength, hindering its application in implant materials such as cardiovascular stents. For cardiovascular stent materials, current mechanical standards require a yield strength (YS) greater than 200 MPa, an ultimate tensile strength (UTS) greater than 300 MPa, and an elongation at break (FE) greater than 20%; this necessitates alloy modification of pure zinc.
[0003] The combination of alloying elements and advanced hot / cold mechanical deformation techniques can significantly improve the strength and ductility of biodegradable zinc alloys. However, a major problem remains in improving the performance of zinc alloys with low alloying and few alloying elements—"strain softening." This effect causes localized deformation in zinc alloys, leading to premature failure. After reaching their maximum stress, the engineering stress-strain curve often shows uneven deformation or necking. Continued deformation beyond the maximum stress (UTS) leads to further stress reduction, resulting in mechanical instability. Strain softening limits the uniform elongation of zinc-based alloys, typically around 5%. For materials subjected to cyclic loads, such as support structures, localized deformation is a serious threat, often leading to premature fracture of the support device. Therefore, uniform elongation should be used as the evaluation index, rather than just the elongation at break.
[0004] Existing technologies all sacrifice strength to improve uniform elongation, which creates a trade-off between strength and plasticity. That is, most alloys only have high strength and low uniform elongation or high uniform elongation and low strength, and cannot achieve high strength and high uniform elongation.
[0005] Meanwhile, for biomedical materials, biosafety is paramount; therefore, the alloying elements must be essential nutrients for the human body. Currently, zinc-based alloys are often modified with metallic elements such as Mg, Ca, Li, Fe, Li, and Ag, as well as rare earth elements like Y. However, the biological effects of rare earth elements like Y on the human body are currently unclear, and they are not suitable for long-term presence in the human body. While adding Ag can activate...<c+a> Dislocations and grain refinement contribute to improved uniform elongation, but also present challenges such as high cost and potential toxicity from high content, making them unsuitable for the preparation of biomedical materials to be implanted in the human body. Furthermore, related research indicates that appropriate heat treatment can mitigate the mechanical instability of alloys and, to some extent, suppress strain softening. However, heat treatment processes are only effective for alloy systems with a heat treatment processing window. Elements such as Mg, Ca, Fe, and Li have almost no solid solubility and cannot be effectively heat treated, making them unsuitable for strain softening modification of zinc-based alloys. Summary of the Invention
[0006] The problem to be solved by this invention is to provide a strain-resistant zinc alloy, its preparation method and application, so as to solve the problem of strain softening of existing zinc-based alloys.
[0007] The technical solution adopted to solve its technical problem is a strain-softening zinc alloy, which comprises the following components by weight percentage: Cu 1.5-2.5%, Mn 0.5-1.2%, and the balance being Zn.
[0008] The beneficial effects of the above-mentioned technical solution of this invention are as follows: The strain-softening zinc alloy of this invention has a multi-scale heterogeneous structure with "bimodal grains + multi-level phase distribution" and a very low initial dislocation density; manganese and copper elements have relatively high solid solubility, and adding a certain amount of manganese and copper elements to the zinc-based alloy can effectively heat treat the zinc-based alloy; at the same time, manganese-rich particles can play a pinning role in the grain boundaries, effectively improving the thermal stability of the alloy structure; the strain-softening zinc alloy of this invention can better resist the significant characteristic of zinc-based alloys - strain softening, and has the characteristics of high strength, toughness and biodegradability.
[0009] Preferably, the strain-resistant zinc alloy includes a bimodal grain and multi-level phase distribution structure.
[0010] Preferably, the bimodal grains include fine grains with an average grain size of 2-5 μm and coarse grains with an average grain size of 10-20 μm; the volume ratio of fine grains in the strain-softening zinc alloy is 30-50%, and the volume ratio of coarse grains is 40-60%.
[0011] More preferably, the multi-level phase distribution structure includes a nanoscale precipitate phase with a particle size of 20–50 nm, a submicron-sized particle phase with a particle size of 500–800 nm, and a micron-sized particle phase with a particle size of 15–20 μm.
[0012] The beneficial effects of the above-mentioned technical solution in this invention are as follows: The multi-level phase distribution structure includes nanoscale precipitates with a particle size of 20-50 nm, submicron-sized phases with a particle size of 500-800 nm, and micron-sized phases with a particle size of 15-20 μm. The submicron and micron-sized phases dynamically promote and inhibit the dynamic recrystallization of the zinc alloy, thereby producing fine dynamically recrystallized grains. Furthermore, the submicron-sized second-phase particles segregate and pin the grain boundaries, effectively preventing grain growth. Grains surrounding the submicron and micron-sized second-phase particles develop fine grains due to particle-induced nucleation (PSN) mechanisms, while grains far from the second-phase particles grow abnormally to form coarse grains. In the bimodal grain structure, the fine grains surrounding the coarse grains contribute to the effective accumulation of geometrically necessary dislocations (GNDs). This bimodal grain structure, composed of fully recrystallized grains and multi-scale distribution of multi-level second-phase particles, greatly stimulates the effective accumulation of GNDs at the heterogeneous interface, resulting in strong heterogeneous deformation-induced (HDI) strengthening and hardening. The interaction between the back stress and the second-phase particles and dislocations further improves the mechanical properties of the zinc alloy. This dual heterogeneous structure effectively overcomes the negative effects of strain softening in high-zinc alloys, significantly increasing strength (YS>280MPa) while effectively improving uniform elongation (>14%). In addition to the strengthening and hardening effect of HDI, the strain-softening resistant zinc alloy of this application has a low critical shear stress (CRSS) for coarse grain twinning, inducing a large number of twins during deformation, thereby effectively hindering grain boundary slip and dislocation movement, adapting to c-axis coordinated deformation, and improving the ductility, toughness, tensile strength, and yield strength of the zinc alloy.
[0013] More preferably, the nano-sized precipitates and the submicron-sized particle size phases are dispersed; the micron-sized particle size phases are layered.
[0014] The present invention also provides a method for preparing the above-mentioned strain-resistant zinc alloy, comprising the following steps:
[0015] (1) Mix pure zinc, zinc-copper intermediate alloy and pure manganese to obtain raw material mixture;
[0016] (2) The raw material mixture is heated and melted at 600-700℃ to obtain an alloy melt;
[0017] (3) Homogenize the alloy melt and then quench and cool it to obtain a pretreated alloy body;
[0018] (4) The pretreated alloy body is heat-insulated and then hot-extruded.
[0019] (5) Heat-treat the alloy body obtained in step (4), cool and then anneal it to obtain the final product.
[0020] The beneficial effects of the above technical solution of the present invention are as follows: The strain-softening zinc alloy prepared by the present invention only needs to be hot extruded once. Under certain temperature, extrusion ratio and extrusion speed, a partially recrystallized structure and a large number of dispersed submicron particles can be obtained. After heat treatment, a strain-softening zinc alloy with a multi-scale heterogeneous structure of "bimodal grains + multi-level phase distribution" with almost complete recrystallization can be obtained.
[0021] Preferably, the homogenization treatment in step (3) is carried out at a temperature of 350-380°C for 5-10 hours.
[0022] Preferably, the temperature of the heat preservation treatment in step (4) is 200-300℃ and the time is 20-40min; the extrusion ratio of the hot extrusion treatment is 11-25:1, the speed is 0.5-2mm / s and the temperature is 150-350℃.
[0023] Preferably, the heat treatment temperature in step (5) is 250-360°C and the time is 0.2-2h.
[0024] This invention also provides the application of the above-mentioned strain-softening zinc alloy in the preparation of cardiovascular stent materials.
[0025] The present invention has the following beneficial effects:
[0026] (1) The strain-softening zinc alloy of the present invention has good yield strength and tensile strength, as well as good fracture elongation and uniform elongation, effectively overcoming the strain softening defects of zinc-based alloys; it can be applied to implant materials such as cardiovascular stent materials that require cyclic load performance.
[0027] (2) The preparation method of the present invention is simple. Only one hot extrusion combined with heat treatment is required to obtain a strain-resistant zinc alloy with a multi-scale heterostructure of "bimodal grains + multi-level phase distribution".
[0028] (3) The strain-resistant zinc alloy of the present invention has strong safety, and the elements composed of the alloy are all essential nutrients for the human body. It is a new type of biodegradable medical alloy material with high prospects and high value. Attached Figure Description
[0029] Figure 1 These are stress-strain curves of the zinc alloys prepared in Example 1 and Comparative Example 1;
[0030] Figure 2 This is a work hardening rate curve of the zinc alloys prepared in Example 1 and Comparative Example 1;
[0031] Figure 3 The image shows the IPF (Integrated Photoform) of the zinc alloy prepared in Comparative Example 1.
[0032] Figure 4 This is the IPF diagram of the strain-softening zinc alloy prepared in Example 1;
[0033] Figure 5 This is an IPF diagram of the tensile fracture surface of the strain-softening zinc alloy prepared in Example 1;
[0034] Figure 6 Orientation difference distribution at the tensile fracture surface of the strain-softening zinc alloy prepared in Example 1;
[0035] Figure 7 This is a scanning electron microscope image of the tensile fracture surface of the strain-softening zinc alloy prepared in Example 1;
[0036] Figure 8 Here is a scanning electron microscope image of the strain-resistant zinc alloy prepared in Example 1;
[0037] Figure 9 This is a transmission electron microscope (TEM) image of the fracture surface of the strain-resistant zinc alloy prepared in Example 1;
[0038] Figure 10 This is a transmission electron microscope (TEM) image of the strain-resistant zinc alloy prepared in Example 1. Detailed Implementation
[0039] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0040] Example 1
[0041] A strain-softening zinc alloy comprising the following components by weight percentage: Cu 2.3%, Mn 0.8%, and balance Zn.
[0042] In this embodiment, the strain-softening zinc alloy includes a bimodal grain and a multi-level phase distribution structure; wherein the bimodal grain includes fine grains with an average grain size of 2.5 μm and coarse grains with an average grain size of 16.4 μm, wherein the volume ratio of fine grains is 35% and the volume ratio of coarse grains is 55%; wherein the multi-level phase distribution structure includes a dispersed nano-sized precipitate with a particle size of 20-50 nm, a dispersed submicron-sized particle size phase with a particle size of 500-800 nm, and a layered micron-sized particle size phase with a particle size of 15-20 μm.
[0043] This embodiment also includes a method for preparing the above-mentioned strain-resistant zinc alloy, comprising the following steps:
[0044] (1) Weigh the ingredients according to the above composition, mix pure zinc, Zn-Cu master alloy and pure manganese to obtain raw material mixture; wherein, the weight percentage of Cu in Zn-Cu master alloy is 5%, and the remainder is Zn;
[0045] (2) The raw material mixture is heated and melted at 650°C to obtain an alloy melt;
[0046] (3) The alloy melt was homogenized at 360°C for 10 hours and then quenched to obtain a pretreated alloy body.
[0047] (4) After the pretreated alloy body is kept at 200℃ for 30 minutes, it is taken out and lubricated with molybdenum disulfide grease. The pretreated alloy body and extrusion die are lubricated after being kept at 200℃. The hot extrusion temperature is set to 200℃, the hot extrusion ratio is 25:1, the hot extrusion rate is 0.5mm / s and a hot extrusion is performed once to obtain a bar with a diameter of 8mm. The bar is then cooled to ambient temperature to maintain its extruded structure.
[0048] (5) The alloy body obtained in step (4) is heat-treated at 330°C for 1 hour, cooled and then annealed to obtain Zn-2.3%Cu-0.8%Mn alloy (weight percentage).
[0049] Example 2
[0050] A strain-softening zinc alloy comprising the following components by weight percentage: Cu 1.5%, Mn 0.5%, and balance Zn.
[0051] In this embodiment, the strain-softening zinc alloy includes a bimodal grain and a multi-level phase distribution structure; wherein the bimodal grain includes fine grains with an average grain size of 3.58 μm and coarse grains with an average grain size of 15.23 μm, wherein the volume ratio of fine grains is 38% and the volume ratio of coarse grains is 52%; wherein the multi-level phase distribution structure includes a dispersed nano-sized precipitate with a particle size of 20-50 nm, a dispersed submicron-sized phase with a particle size of 500-800 nm, and a layered micron-sized phase with a particle size of 15-20 μm.
[0052] This embodiment also includes a method for preparing the above-mentioned strain-resistant zinc alloy, comprising the following steps:
[0053] (1) Weigh the ingredients according to the above composition, mix pure zinc, Zn-Cu master alloy and pure manganese to obtain raw material mixture; wherein, the weight percentage of Cu in Zn-Cu master alloy is 5%, and the remainder is Zn;
[0054] (2) The raw material mixture is heated and melted at 640°C to obtain an alloy melt;
[0055] (3) The alloy melt was homogenized at 350°C for 10 hours and then quenched to obtain a pretreated alloy body.
[0056] (4) After the pretreated alloy body is kept at 300℃ for 20 minutes, it is taken out and lubricated with molybdenum disulfide grease. The pretreated alloy body and extrusion die are lubricated after being kept at 300℃. The hot extrusion temperature is set to 250℃, the hot extrusion ratio is 16:1, the hot extrusion rate is 1mm / s and a hot extrusion is performed once to obtain a bar with a diameter of 10mm. The bar is then cooled to ambient temperature to maintain its extruded structure.
[0057] (5) The alloy body obtained in step (4) is heat-treated at 280°C for 2 hours, cooled and then annealed to obtain Zn-1.5%Cu-0.5%Mn alloy (weight percentage).
[0058] Example 3
[0059] A strain-softening zinc alloy comprising the following components by weight percentage: Cu 1.8%, Mn 0.6%, and balance Zn.
[0060] In this embodiment, the strain-softening zinc alloy includes a bimodal grain and a multi-level phase distribution structure; wherein the bimodal grain includes fine grains with an average grain size of 4.82 μm and coarse grains with an average grain size of 16.33 μm, wherein the volume ratio of fine grains is 45% and the volume ratio of coarse grains is 50%; wherein the multi-level phase distribution structure includes a dispersed nano-sized precipitate with a particle size of 20-50 nm, a dispersed submicron-sized phase with a particle size of 500-800 nm, and a layered micron-sized phase with a particle size of 15-20 μm.
[0061] This embodiment also includes a method for preparing the above-mentioned strain-resistant zinc alloy, comprising the following steps:
[0062] (1) Weigh the ingredients according to the above composition, mix pure zinc, Zn-Cu master alloy and pure manganese to obtain raw material mixture; wherein, the weight percentage of Cu in Zn-Cu master alloy is 5%, and the remainder is Zn;
[0063] (2) The raw material mixture is heated and melted at 620°C to obtain an alloy melt;
[0064] (3) The alloy melt was homogenized at 380°C for 5 hours and then quenched to obtain a pretreated alloy body.
[0065] (4) After the pretreated alloy body is kept at 200℃ for 40 minutes, it is taken out and lubricated with molybdenum disulfide grease. The pretreated alloy body and extrusion die are lubricated after the heat treatment. The hot extrusion temperature is set to 300℃, the hot extrusion ratio is 11:1, the hot extrusion rate is 2mm / s and a hot extrusion is performed once to obtain a bar with a diameter of 12mm. It is then cooled to ambient temperature to maintain its extruded structure.
[0066] (5) The alloy body obtained in step (4) is heat-treated at 360°C for 0.25 h, cooled and then annealed to obtain Zn-1.8%Cu-0.6%Mn alloy (weight percentage).
[0067] Comparative Example 1
[0068] A zinc alloy comprising the following components by weight percentage: Cu 2.3%, Mn 0.8%, and balance Zn.
[0069] This comparative example also includes the preparation method of the above-mentioned zinc alloy, comprising the following steps:
[0070] (1) Weigh the ingredients according to the above composition, mix pure zinc, Zn-Cu master alloy and pure manganese to obtain raw material mixture; wherein, the weight percentage of Cu in Zn-Cu master alloy is 5%, and the remainder is Zn;
[0071] (2) The raw material mixture is heated and melted at 650°C to obtain an alloy melt;
[0072] (3) The alloy melt was homogenized at 360°C for 10 hours and then quenched to obtain a pretreated alloy body.
[0073] (4) After the pretreated alloy body is kept at 200℃ for 30 minutes, it is taken out and lubricated with molybdenum disulfide grease. The pretreated alloy body and extrusion die are then lubricated. The hot extrusion temperature is set to 200℃, the hot extrusion ratio is 25:1, and the hot extrusion rate is 0.5mm / s. One hot extrusion is then performed to obtain a bar with a diameter of 8mm. The bar is then cooled to ambient temperature.
[0074] Experimental Example
[0075] The strain-resistant zinc alloy obtained by the preparation method of the present invention, under specific temperature, extrusion ratio and extrusion speed, has a partially recrystallized structure and a large number of dispersed submicron particles; after heat treatment, a multi-scale heterostructure of "bimodal grains + multi-level phase distribution" is obtained.
[0076] 1. The yield strength, tensile strength, uniform elongation, and elongation at break of strain-softening zinc alloys are used as key evaluation indicators. A microcomputer-controlled electronic universal testing machine (model: UTM5105SLXY) is used to test the specimens (size: 21*3*1.5mm) according to the tensile testing method for metallic materials (GB / T228-2010) at a 1×10⁻⁶ Ω·cm. -4Under different strain rates, the engineering stress-strain curves were measured. The yield strength can be obtained by drawing a parallel line to the elastic stage at 0.2% strain. For heat-treated samples with a distinct yield plateau, the yield point is the stress value corresponding to the plateau. The tensile strength is the stress value corresponding to the highest point on the curve. The uniform elongation is the strain corresponding to the tensile strength. The elongation at break is the maximum strain value at which the curve breaks. The results are as follows: Figures 1-2 As shown. From Figure 1 As can be seen, the strain-softening resistant zinc alloy prepared by this invention has an excellent combination of high yield strength (287.8 MPa) and high uniform elongation (14.1%), significantly improving the strain softening phenomenon. Its mechanical properties meet the standards for medical device implantation; it can be used to prepare orthopedic load-bearing materials (such as bone screws and plates), tissue closure materials (such as anastomotic screws), cardiovascular stents, etc. Figure 2 As can be seen, compared with the zinc alloy prepared by hot extrusion only in Comparative Example 1, the strain-softening zinc alloy prepared in Example 1 has an additional work hardening stage after hot extrusion and heat treatment, which may be an important reason for its high strength and high uniform elongation.
[0077] 2. The microstructure (alloy orientation distribution and grain size information) of the zinc alloys prepared in Example 1 and Comparative Example 1 was tested. The alloys were characterized using backscattered electron diffraction (EBSD) combined with scanning electron microscopy, and the results were analyzed using AZtecCrystal or Channel 5 software. The results are as follows: Figures 3-6 As shown. Figures 3-4 Comparative analysis reveals that the extruded alloy exhibits a partially recrystallized structure, mostly consisting of fine grains with a small amount of coarse subgrains, containing a high dislocation density. Most of its grains exhibit deformation textures of <10-10> / / ED (ED represents the extrusion direction) and <11-20> / / ED. For the heat-treated alloy, the grains are significantly larger, with the grain size near the second phase (>1 μm) being much smaller than that further away, exhibiting a bimodal structure. Furthermore, most grains show a typical <11-20> / / ED recrystallization texture, indicating a significant transformation in texture after heat treatment. Additionally, a layered distribution of the micron-sized second phase along the extrusion direction can be observed. Analysis of the microstructure at the fracture surface formed by tensile testing of the strain-softening zinc alloy prepared in Example 1 shows… Figure 5 In Example 1, the strain-softening zinc alloy exhibits twinning. The formation of twins can coordinate the c-axis to accommodate plastic deformation while simultaneously hindering dislocation slip, further improving the work hardening rate. Twins also appeared in the strain-softening zinc alloy during tensile deformation, further demonstrating the significant contribution of twins to plastic deformation. The twins were characterized using EBSD orientation difference analysis combined with TEM morphology observation and diffraction pattern analysis, such as... Figure 6 and Figure 9As shown, the twins and the matrix exhibit an orientation angle of 86.5°±5°, demonstrating the activation of numerous stretched twins.
[0078] 3. The microstructure of the strain-softening zinc alloy at the tensile fracture surface prepared in Example 1 was characterized, and the results are as follows: Figure 7 As shown. From Figure 7 As can be seen from the results, the strain-softening zinc alloy prepared in Example 1 has a large number of dimples at the tensile fracture surface, indicating that it has good tensile plasticity.
[0079] 4. Scanning electron microscopy (SEM) images of the strain-softening zinc alloy prepared in Example 1 after polishing and etching were taken, as shown below. Figure 8 As shown; from Figure 8 It can be seen that the strain-resistant zinc alloy contains micron-sized second phases and submicron-sized phases.
[0080] 5. The fracture surface of the strain-softening resistant zinc alloy prepared in Example 1 was characterized by transmission electron microscopy, and the results are as follows: Figure 10 As shown; from Figure 10 It can be seen that nanoscale precipitates exist in the strain-softening zinc alloy.
[0081] 6. The mechanical properties of zinc-based alloys in Comparative Example 1, Comparative Example 1, and existing reports are shown in Table 1. As can be seen from Table 1, the strain-softening resistant zinc alloy obtained by this invention exhibits good yield strength, tensile strength, and uniform elongation. It maintains a uniform elongation within the range of 10-20% while ensuring a yield strength >200 MPa and a tensile strength >300 MPa. This effectively solves the problem of strain softening in zinc-based alloys and can be well applied to implant materials such as cardiovascular stents. It overcomes the problem of premature failure of zinc-based alloys during service (especially under cyclic loading) and achieves a balance between high strength and high uniform elongation.
[0082] Table 1 Comparison of mechanical properties of zinc-based alloys
[0083]
[0084] Literature 1: Tang, Zibo, et al. Potential biodegradable Zn-Cu binary alloys developed for cardiovascular implant applications. Journal of the mechanicalbehavior of biomedical materials. 72 (2017) 182-191.
[0085] Document 2: Chen, Chun, et al. Biodegradable Zn-1.5Cu-1.5Ag alloy with anti-aging ability and strain hardening behavior for cardiovascular stents. Materials Science and Engineering: C. 116(2020)111172.
[0086] Document 3: Tang, Zibo, et al. Design and characterizations of novel biodegradable Zn-Cu-Mg alloys for potential biodegradable implants. Materials & Design. 117(2017)84-94.
[0087] Document 4: Huang, Shiyu, et al. In vitro degradation behavior of novel Zn-Cu-Li alloys: roles of alloy composition and rolling processing. Materials & Design. 212(2021)110288.
[0088] Document 5: Lin, Jixing, et al. Biodegradable Zn-3Cu and Zn-3Cu-0.2Ti alloys with ultrahigh ductility and antibacterial ability for orthopedic applications. Journal of Materials Science & Technology. 68(2021)76-90.
[0089] Document 6: Sun, Shineng, et al. Abnormal effect of Mn addition on the mechanical properties of as-extruded Zn alloys. Materials Science and Engineering: A. 701(2017)129-133.
[0090] Document 7: Chen, Hong-Ting, Zhang-Zhi Shi, and Xue-Feng Liu. Microstructure and mechanical properties of extruded and caliber rolled biodegradable Zn-0.8Mn-0.4Ag alloy with high ductility. Materials Science and Engineering: A.770(2020)138543.
[0091] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any way. All technical solutions obtained by equivalent substitution or equivalent transformation fall within the scope of the present invention.
Claims
1. A zinc alloy resistant to strain softening, characterized in that, The strain-softening zinc alloy comprises, by weight percentage: Cu 1.5~2.5%, Mn 0.5~1.2%, with the balance being Zn; the strain-softening zinc alloy comprises a bimodal grain and multi-level phase distribution structure; The strain-resistant zinc alloy is prepared by the following method: (1) Mix pure zinc, zinc-copper intermediate alloy and pure manganese to obtain raw material mixture; (2) The raw material mixture is heated and melted at 600~700℃ to obtain an alloy melt; (3) The alloy melt is homogenized and then quenched and cooled to obtain a pretreated alloy body; the homogenization treatment temperature is 350~380℃ and the time is 5~10h. (4) The pretreated alloy body is heat-insulated and then hot-extruded; the heat-insulation temperature is 200~300℃ and the time is 20~40min; the extrusion ratio of the hot extrusion is 11~25:1, the speed is 0.5~2mm / s and the temperature is 150~350℃. (5) The alloy body obtained in step (4) is subjected to heat treatment, cooled and then annealed to obtain the alloy body. The heat treatment temperature is 250~360℃ and the time is 0.2~2h.
2. The strain-softening zinc alloy as described in claim 1, characterized in that, The bimodal grains include fine grains with an average grain size of 2-5 μm and coarse grains with an average grain size of 10-20 μm; the volume ratio of fine grains in the strain-resistant zinc alloy is 30-50%, and the volume ratio of coarse grains is 40-60%.
3. The strain-softening zinc alloy as described in claim 1, characterized in that, The multi-level phase distribution structure includes a nanoscale precipitate phase with a particle size of 20-50 nm, a submicron-sized particle phase with a particle size of 500-800 nm, and a micron-sized particle phase with a particle size of 15-20 μm.
4. The strain-softening zinc alloy as described in claim 3, characterized in that, The nanoscale precipitates and submicron-sized particles are dispersed; the micron-sized particles are layered.
5. The application of the strain-softening zinc alloy according to any one of claims 1 to 4 in the preparation of cardiovascular stent materials.
Citation Information
Patent Citations
Biomedical Zn-Mn-Cu zinc alloy and preparation method thereof
CN107198796A
Medical Zn-Cu-Mn-Zr alloy capable of being degraded in living body and high in strength and toughness
CN112430764A